Process Architecture for the Integration of Outpatient, Hospitalization and Emergency Services in Level III Hospitals in Peru - Albornoz, Miguel (2024)
Peru has a fragmented health system, which limits access to its health services because the people seeking medical services can only be treated in specified health centers that are determined by their health insurance. Additionally, this causes each health provider to count and manage their processes and information in an isolated and independent manner. In the Peruvian case, this generates an overload in public health services, since, of the 83.3% of insured nationwide, 73.1% belong to the public sector. Therefore, a process architecture is presented, based on the Zachman framework, that integrates the processes of health services (outpatient, hospitalization and emergencies), as well as an Information Technology (IT) process that supports them. The architecture aims to ensure that level III hospitals in Peru have standardized processes and information, as well as to guarantee their application regardless of the hospital regime. The processes were designed based on information from two Peruvian level III hospitals, belonging to the Sistema Integrado de Salud (SIS) and Seguro Social de Salud (EsSalud). A time simulation of the current processes and those proposed by the architecture, show an average improvement percentage of 69% in the outpatient process, 27% in emergencies and 7% in hospitalization. In addition, an expert judgment was made obtaining a very high assessment on the usefulness of the architecture.